Determinan Perilaku Keluarga dalam Melatih Range of Motion pada Pasien Pasca Stroke - Kissy Annida Puruhita; Sodikin Sodikin (Faletehan Health Journal, 2024)
Stroke is a non-traumatic circulatory disorder that results in insufficient blood and oxygen supply to the brain. Stroke patients often experience long-term basic functional impairments. Families can play a direct caregiving role for post-stroke patients, including range of motion (ROM) exercises. The purpose of this study was to identify the determinants of family behavior in training ROM for post-stroke patients. This research was an analytical survey with a cross-sectional approach. The sample consisted of 76 family members who cared for stroke patients in the last 3 months at Lily Room of Dr. R. Goeteng Taroenadibrata Regional General Hospital, Purbalingga. The research instrument was a questionnaire. The study results indicated a strong correlation between knowledge (p-value 0.007, OR 6.9), attitude (p-value 0.000, OR 11.1), self-efficacy (p-value 0.001, OR 0.16) and social support (p-value 0.000, OR 0.02) with behavior in training ROM for post-stroke patients. Healthcare professionals should educate family members about factors influencing behavior in training ROM for post-stroke patients at home to ensure optimal recovery for the patients.